Experts’ perspectives on the application of public-private partnership policy in prevention of road traffic injuries - Azami-Aghdash, Saber (Chin J Traumatol, 2020)
PURPOSE: Successful application experiences on public-private partnership (PPP) in different countries, suggest that PPP could be an option in road traffic injury (RTI) prevention. The present study aims at investigating the applicability of PPP policy in RTI prevention in Iran based on the experts’ perspectives. METHODS: This is a qualitative study with grounded theory approach which has been conducted in Tabriz University of Medical Sciences, Iran in 2018. The participants were 22 experts in the field of RTIs selected using purposive sampling method. Data were collected by semi-structured interviews and analyzed with content-analysis method. RESULTS: The results were classified under 5 main themes (applicability, scopes and services, challenges, advantages, and strategies) for applying PPP policy and 37 sub-themes. Due to the prevalence of RTIs, the present challenges in public sector, existence of qualified private sector, and successful experiences in other areas, there are opportunities for private sector partnership in prevention of RTIs. Private sector could participate in different scopes and services regarding RTI prevention, including road construction and maintenance, maintenance and provision of vehicles safety and public education. The main challenges including legislation issues, ambiguities in collaboration, political and organizational unsustainability, government's financial hardship and lack of experienced experts in the field of RTI. However, there are significant advantages including high efficiency in program implementation, covering the weaknesses of public sector, effective and efficient management on application of PPP in RTI prevention. The strategies include identifying and prioritizing the assignable activities, identifying the qualified private sector, developing PPP policies and legal frameworks, creating a common language between public and private parties, trying to meet the expectations of the private sector by public sector, developing a comprehensive and sound contract, and cultivating public culture to accept private sector in the field of RTI prevention. CONCLUSION: This study sought to determine whether PPP could be used as strategy to reduce the burden of RTIs in Iran. But it requires a lot of preliminary studies to provide the context and conditions for applying this policy.